Moldovan family farms: social buffer or economic driver? A survey-based assessment - Piras, Simone <1986> (Alma Mater Studiorum - Università di Bologna, 2016)

(untitled)
After obtaining independence from the USSR in 1991, the Republic of Moldova carried out an insider privatization of the land belonging to former Soviet collective farms. As a result, almost 900,000 small family farms emerged, the majority of whom are still active today. Although they play an important socioeconomic role, policy makers neglect them as a residual, shrinking phenomenon. By adopting the theoretical perspective of peasant economics, this dissertation aims at assessing the health status of these farms over ten years after the land reform, and their evolution over time. Data from an original mixed quantitative and qualitative survey carried out on a sample of 126 farms in spring 2015, and the databases of the Household Budget Survey for the period 2006-2013 are used. The main drivers of farmers’ livelihood choices are identified by means of a 31-item Likert scale, and a comprehensive picture of the typical family farm is drawn. Farms are then grouped according to land size, level of commercialization and location, and their evolution over time is analyzed by means of Markov transition chains and multinomial logistic regressions. A focus on production strategies follows. Finally, the impact of agriculture on poverty levels and the implications of alternative livelihood choices are assessed by means of counterfactual incomes and life levels calculated through propensity score matching. It emerges that families were allocated land plots without the tools for working them. Therefore, they adopt low-input, labour-intensive production strategies and are mainly subsistence-oriented. Farm income, although small, plays a key role in relieving vulnerable people from poverty, so that land is a fundamental social buffer. Moreover, home food production is important for social and self-appraisal. For these reasons, an agricultural development strategy based on farm intensification rather than growth and on leasing rather than sale of land is proposed. === Dopo l’indipendenza dall’URSS (1991), la Moldavia ha privatizzato le terre delle fattorie collettive distribuendo voucher ai lavoratori. Questo processo ha generato circa 900.000 piccole aziende familiari, in maggioranza ancora attive. Benché rivestano un’importante funzione socioeconomica, queste sono trattate dalle istituzioni come un fenomeno residuale e in esaurimento. Adottando il punto di vista della peasant economy, questa tesi si ripropone di valutarne lo stato di salute a distanza di oltre dieci anni dalla riforma agraria. A tal fine, vengono utilizzati i dati raccolti dall’autore attraverso un’indagine realizzata nella primavera 2015 su un campione di 126 famiglie e le banche dati dell’Indagine sui Redditi delle Famiglie per il 2006-2013. In primo luogo, si identificano le motivazioni degli agricoltori e viene presentata una descrizione densa della tipica famiglia contadina. Successivamente, queste sono raggruppate secondo la terra posseduta, il livello di commercializzazione e la posizione geografica, e la loro evoluzione è analizzata usando matrici di transizione di Markov ed equazioni logistiche multinomiali. Segue un focus sulle strategie di produzione. Infine, l’impatto dell’agricoltura sulla povertà e le implicazioni di diverse strategie di sopravvivenza sono analizzati attraverso i redditi teorici calcolati con il propensity score matching. Emerge che le famiglie hanno ricevuto la terra ma non i mezzi per lavorarla, per cui sono costrette ad adottare tecniche di produzione ad alta intensità di lavoro e bassa intensità di capitale, e producono quasi esclusivamente per l’autoconsumo. Il reddito agricolo aiuta le famiglie vulnerabili a combattere la povertà, per cui la terra rappresenta uno strumento di welfare. Inoltre, la capacità di produrre cibo e la proprietà terriera sono motivo di autorealizzazione e generano considerazione sociale. Per questi motivi, si suggerisce una strategia di sviluppo agricolo che punti sull’intensificazione della produzione piuttosto che sulla concentrazione della proprietà e che agevoli l’affitto delle terre piuttosto che la loro vendita. === После провозглашения в 1991 году независимости, Республика Молдова провела процесс приватизации земли принадлежащей бывшим советским колхозам. Таким образом, появились почти 900.000 небольших семейных ферм, из которых многие ещё функционируют. Несмотря на то, что эти фермы играют важную социально-экономическую роль, законодатели пренебрегают ими, так как видят в них устаревший феномен, который скоро исчезнет. Приняв точку зрения теории крестьянского хозяйства, эта диссертация посвящена оценке состояния здоровья семейных хозяйств, за десять лет после принятия земельной реформы, и их эволюции во времени. Были использованы данные, собранные с помощью опроса, проведённого автором весной 2015 на образце 126 семей и базы данных Обследования Бюджетов Домашних хозяйств на 2006-2013 годы. Прежде всего, была выявлена мотивация фермеров с помощью 31 – балльной шкале Лайкерта, а также была представлена всеобъемлющая картина типичной семейной фермы. Затем, фермы были сгруппированы в соответствии с размером земельного участка, уровнем коммерциализации и географическим расположением. Их эволюция анализирована с помощью Марковских переходных цепей и мультиноминальных логистических регрессий. Следует анализ сфокусированный на стратегиях производства. Также анализируется, с помощью теоретических доходов которые были выявлены с использованием методологий propensity score matching, влияние сельского хозяйства на уровень бедности и последствия различных стратегий выживания. Выясняется, что семьям были выделены земельные участки без инструментов для обрабатывания их, поэтому они вынуждены выбрать для себя методы производства которые включают в себя интенсивные трудовые показатели при маленьких затрат и производят почти исключительно для собственного потребления. Доходы от семейных ферм, даже если они маленькие, играют ключевую роль в освобождении уязвимых групп населения от бедности, таким образом, земля является основным социальным амортизатором. Кроме того, производство домашних продуктов и владение землёй являются причиной для самореализации и порождает социальную позитивную оценку. По этим причинам, предлагается стратегия развития сельского хозяйство которое обратит внимание больше на интенсификации производства чем на увеличения размера земельных участков в собственности и на способствования арендования земли, а не на её продажу.